Child Death due to Neglect a Case Report - Dokgöz, Halis; Şam, Bülent; Ersoy, Gökhan; Müsellim, Nurşen Turan (The Bulletin of Legal Medicine, 2002)
The child neglect, as a form of child abuse, means that primary requirements of a child like feeding, health, shelter, clothing, protection and care are not met by the family and by the government institution including health, education, and social security. The neglect can be encountered in the forms of physical, emotional and or medical. Serious neglect might result in death. In Turkey, scientific studies regarding the frequency and quality of the child neglect are not sufficient Although neglect is more common than physical abuse death or severe injury occurs, unless it is not treated seriously. This case is a one and a half years old, boy 66 cm in height and 4050 g in weight, cachectic. He has a wide inflamated sore in his genital region. His physical development both in height and weight were retarded in compare to the normal percentile Lobular pneumonia with abcesses and purulent bronchiolitis in the lungs, diffuse lipidosis in the hver and villus ghosts in the otolytic intestine epithelia are found in histopathologic examination. The cause of death was determined as respiratory failure as a consequence of lobular pneumonia and purulent bronchiolitis. This case is presented in order to take notice of the significance of prevention and early diagnosis of child neglect. Key words: Child abuse, neglect, death.